Influence of Service Quality on Customer Loyalty at BSI KCP Imam Bonjol, Aceh Barat Regency - Nur Fajri; Ahmad Arkadius; Sri Hartati; Meri Saputra (LPPM Politeknik Aceh Selatan, 2023)
This study aims to determine the effect of service quality on customer loyalty at BSI KCP Imam Bonjol Kabupaten Aceh Barat. The dependent variable in this study is customer loyalty while the independent variable is service quality. The data analysis method used in this study uses the classic assumption test including the normality test, multicollinearity test, heteroscedestity test and autocorrelation test. Meanwhile, hypothesis testing includes multiple linear tests, partial t tests and simultaneous F. Based on the results of the study using the Anova test (F test) shows that the sig value <0.05, in other words H0 rejects, means that service quality affects customer loyalty of BSI KCP Imam Bonjol Kabupaten Aceh Barat.